Experimental and numerical studies on the flexural behavior of fibre reinforced concrete beams with innovative hybrid FRP-wrapped steel bars. Issue 5 (3rd September 2021) - Subbaram, Sivaramakrishnan; Komarasamy, Chinnaraju
ABSTRACT: The durability and lifespan of concrete structures are significantly affected by the corrosion of steel reinforcement. Though epoxy-coated steel reinforcement is being used for practical applications, slight damage in the coating during the construction process is enough to initiate the corrosion process. The shortcomings in the current practices to prevent corrosion of steel reinforcement have led the researchers to look for alternatives. Innovative hybrid reinforcing elements with solid steel core and fibre-reinforced polymer (FRP) wrapping (called steel–FRP composite bars (SFCB)) can be considered as a suitable alternative to conventional steel reinforcement. In this research paper, experimental and numerical studies that investigated the flexural behaviour of concrete beam specimens reinforced with SFCB produced using glass fibres or carbon fibres are presented and discussed. Experimental study consisted of flexural testing of six concrete beam specimens with conventional steel reinforcement or SFCB with glass fibres or SFCB with carbon fibres. Two different spacings of shear stirrups were considered. Failure mode, first crack load, ultimate flexural load and load-deflection behaviour were recorded during the experiment. The test results showed that beam specimens with SFCB reinforced achieved less ultimate flexural load as compared to beam specimens with conventional steel reinforcement. The failure mode was found to be influenced by the spacing of the shear stirrups. The results of the numerical analysis were close to the experimental results. .